2018
DOI: 10.1055/a-0752-4224
|View full text |Cite
|
Sign up to set email alerts
|

Association of Trunk Rotational Velocity with Spine Mobility and Curvatures in Para Table Tennis Players

Abstract: This study investigates the relationship of trunk rotational velocity with mobility and curvature of the spine in wheelchair table tennis players. Eleven para table tennis players and 13 able-bodied athletes performed 5 seated trunk rotations to each side with 1 kg barbell placed on the shoulders. Trunk rotational velocity and respective angular displacement were significantly lower in para table tennis players compared to able-bodied athletes. Both groups showed similar values of thoracic kyphosis. However, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The area at the front of the court is the most vulnerable part, and it relates to the offensive game strategy (Phomsoupha & Laffaye, 2015;Strapasson et al, 2017;Ribeiro & Almeida, 2020). The decision to use this strategy in PBd can be explained by the difficulty in reaching the shuttle due to the sitting position and the players' trunk flexion difficulties, common in wheelchair players (Beckman et al, 2017;Zemková, Muyor & Jeleň, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The area at the front of the court is the most vulnerable part, and it relates to the offensive game strategy (Phomsoupha & Laffaye, 2015;Strapasson et al, 2017;Ribeiro & Almeida, 2020). The decision to use this strategy in PBd can be explained by the difficulty in reaching the shuttle due to the sitting position and the players' trunk flexion difficulties, common in wheelchair players (Beckman et al, 2017;Zemková, Muyor & Jeleň, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The disability of these athletes participating in Paralympic court sports may impact their sporting performance [ 17 ]. For instance, wheelchair table tennis players exhibit lower mobility in the thoracic and lumbar regions of the spine during trunk flexion as well as lower lumbar inversion and pelvic retroversion than able-bodied athletes [ 18 ]. Their decreased posterior concavity and limited range of motion during trunk rotations contribute to lower trunk rotational velocity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that posterior hip extension and flexion, external knee rotation and anterior hip extension and flexion were significantly greater in the professional athletes compared to the amateur group. Zemková et al [8] explored the relationship between trunk rotation velocity and spinal mobility and curvature in wheelchair table tennis players. The results showed that the trunk rotation velocity and the corresponding angular displacement were significantly lower in wheelchair table tennis players compared to healthy athletes.…”
Section: Introductionmentioning
confidence: 99%